Peripheral Hemolysis in Relation to Iron Rim Presence and Brain Volume in Multiple Sclerosis - Krajnc, Nik; Bsteh, Gabriel; Kasprian, Gregor; Zrzavy, Tobias; Kornek, Barbara; Berger, Thomas; Leutmezer, Fritz; Rommer, Paulus; Lassmann, Hans; Hametner, Simon; Dal-Bianco, Assunta (Frontiers in Neurology, 2022)
Background. Iron rim lesions (IRLs) represent chronic lesion activity and are associated with a more severe disease course in multiple sclerosis (MS). How the iron rims around the lesions arise in patients with MS (pwMS), and whether peripheral hemolysis may be a source of iron in rim associated macrophages, is unclear. Objective. To determine a potential correlation between peripheral hemolysis parameters and IRL presence in pwMS. Methods. This retrospective study included pwMS, who underwent a 3T brain MRI between 2015 and 2020 and had a blood sample drawn at +/-2 weeks. Patients with vertigo served as a control group. Results. We analyzed 75 pwMS (mean age 37.0 years [SD 9.0], 53.3% female) and 43 controls (mean age 38.3 years [SD 9.8], 51.2% female). Median number of IRLs was 1 (IQR 4), 28 (37.3%) pwMS had no IRLs. IRL patients showed significantly higher Expanded Disability Status Scale (EDSS) compared to non-IRL patients (median EDSS 2.3 [IQR 2.9] vs. 1.3 [IQR 2.9], p=0.017). Number of IRLs correlated significantly with disease duration (rs=0.239, p=0.039), EDSS (rs=0.387, p<0.001) and Multiple Sclerosis Severity Scale (MSSS) (rs=0.289, p=0.014). There was no significant difference in hemolysis parameters between non-IRL, IRL patients (regardless of gender and/or disease type) and controls, nor between hemolysis parameters and the number of IRLs. Total brain volume was associated with fibrinogen (β= -0.34, 95% CI -1.32– -0.145, p=0.016), and absolute cortical and total grey matter volumes were associated with hemoglobin (β=0.34, 95% CI 3.39–24.68, p=0.011; β=0.33, 95% CI 3.29–28.95, p=0.015; respectively). Conclusion. Our data do not suggest an association between hemolysis parameters and IRL presence despite a significant association between these parameters and markers for neurodegeneration.